2021
DOI: 10.1080/00365521.2021.1961307
|View full text |Cite
|
Sign up to set email alerts
|

Chronic constipation is negatively associated with colonic diverticula

Abstract: Objectives: Constipation has been considered the key risk factor for diverticulosis occurrence, although the underlying mechanism is unclear. We investigated the factors associated with diverticulosis, focusing on the association of constipation severity with the localization and number of diverticula. Materials and methods:We analyzed consecutive patients who underwent colonoscopy between March and December 2019. Chronic constipation was diagnosed as constipation meeting Rome Ⅳ criteria or as that requiring l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Contrary to these beliefs, recent cross-sectional studies have found that constipation and a low-fiber diet were not associated with diverticulosis. 23 25 A cross-sectional study also found no association between diverticulosis and straining or incomplete bowel movements. 24 Instead, individuals with more frequent bowel movements were more likely to have diverticulosis.…”
Section: Discussionmentioning
confidence: 98%
“…Contrary to these beliefs, recent cross-sectional studies have found that constipation and a low-fiber diet were not associated with diverticulosis. 23 25 A cross-sectional study also found no association between diverticulosis and straining or incomplete bowel movements. 24 Instead, individuals with more frequent bowel movements were more likely to have diverticulosis.…”
Section: Discussionmentioning
confidence: 98%
“…Demographic and comorbidity data were obtained using a questionnaire. Chronic constipation was diagnosed based on Rome IV criteria for functional constipation 36 . The severity of constipation was measured using the Constipation Scoring System (CSS; range 0–30) 37 .…”
Section: Methodsmentioning
confidence: 99%
“…Chronic constipation was diagnosed based on Rome IV criteria for functional constipation. 36 The severity of constipation was measured using the Constipation Scoring System (CSS; range 0-30). 37 In another questionnaire, data concerning colonoscopy and BP were obtained on the day of colonoscopy.…”
Section: Data Collectionmentioning
confidence: 99%